Sweden : Financial Sector Assessment Program Update: Detailed Assessment of Observance on CPPS Core Principles for Systemically Important Payment (RIX). (IMF Staff Country Reports; Country Report ;, 2011)
The Riksbank (RB) has conducted a formal self-assessment of the RIX system's observance of the Core Principles in the context of the IMF Financial Sector Assessment Program, which describes the role of Riksbank-Funds Transfer System (RIX) in maintaining the stability of the Swedish financial system. Riksbank's Funds Transfer System (RIX) provides facilities for real-time gross settlement (RTGS) in central bank money of Swedish kronor (SEK) payment transactions. The assessment points to opportunities for further improvements in the legal basis and in clearly defining and publicly disclosing its major policies.